THE STUDY OF WRITTEN FEEDBACK ON STUDENTS EFL WRITING OF THE TWELFTH GRADE STUDENTS OF SMK N 1 SERIRIT IN THE ACADEMIC YEAR 2015/2016 - ., Ni Putu Novita S Dewi; ., Putu Eka Dambayana S., S.Pd.; ., Nyoman Karina Wedhanti, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk (1) mengidentifikasi written feedback yang ideal dalam tulisan berbahasa inggris siswa. (2) mengidentifikasi respon – respon siswa terhadap written feedback yang diberikan guru terhadap tulisan berbahasa inggris siswa. Identifikasi terhadap written feedback yang ideal ditinjau berdasarkan theory dari Nicol (2010). Identifikasi terhadap respon – respon siswa terhadap written feedback ditinjau berdasarkan theory dari Gibbs and Simpson (2003). Subjek dari penelitian ini adalah guru dan siswa –siswa di kelas XII AP 1 di SMK N 1 Seririt. Penelitian ini adalah penelitian survai. Instrumen yang digunakan dalam penelitian ini adalah peneliti peneliti itu sendiri, dokumentasi, panduan wawancara dan angket. Data diperoleh dengan mengumpulkan dokumentasi siswa, panduan interview dan angket. Hasil dari penelitian menunjukkan bahwa ada enam karakteristik yang digunakan guru dalam pemberian written feedback yaitu understandable, selective, specific, timely, balanced and forward looking. Penelitian ini juga difokuskan dengan respon – respon siswa terhadap written feedback. Penelitian ini menggunakan tiga skala untuk mengukur respon – respon siswa terhadap written feedback. Tiga skala tersebut diantaranya jumlah dan waktu dari written feedback, kualitas dari written feedback dan kegunaan dari written feedback. Penelitian ini menemukan bahwa siswa menyadari akan pentingnya written feedback dalam menulis. Penelitian ini diharapkan kepada guru bahasa inggris untuk mengaplikasikan sebuah written feedback yang ideal. Kata Kunci : feedback, written feedback dan respon siswa ABSTRACT This study was aimed at (1) identify the ideal written feedback on the students’ EFL writing in SMKN 1 Seririt and (2) identify the students’ responses toward written feedback given by the teacher towards their EFL writing in SMKN 1 Seririt. The identification of ideal written feedback characteristics was crosschecked with the theory of Nicol (2010). The identification of students’ responses towards written feedback was crosscheck with the theory of Gibbs and Simpson (2003). The subjects of the study were a teacher and thirty nine students at XII AP 1 class of SMK N 1 Seririt. This study was a survey research. The instruments used in collecting the data were the researcher herself, documentation, interview guide and questionnaire. The data were gathered by collecting the students’ documentation, interview and questionnaire. The result of the study showed that there are six ideal characteristics of written feedback that the teacher used in giving written feedback namely understandable, selective, specific timely, balanced and forward looking. This also focused on students’ responses towards written feedback. This study used three scales to measure the students’ responses towards written feedback. The three scales were (1) quantity and timing of written feedback (2) quality of written feedback (3) use of written feedback. The triangulate data of this study found that the students’ got an ideal written feedback. This study also found that the students realize that written feedback was useful for their writing. This study is expected to English teacher to apply an ideal written feedback. keyword : feedback, written feedback and students’ responses